How do you mainstream occupational safety and health successfully into education? Key elements to teach prevention in schools - Burgos García, Antonio (Profesorado, Revista de Currículum y Formación del Profesorado, 2010)
This article shows the key elements to teach prevention work in schools. In this sense, this initiative is determined by the European and Spanish Strategy for Health and Safety at Work (2007-2012), First Andalusian Plan Occupational Heal th and Safety of teachers in public schools dependent on the Regional Government of the Junta de Andalusia (2006-2010) and the Andalusian Strategy on Safety and Health at Work (2010-2014). The purpose of this paper is to present a theoretical and reflective contributi on extracted from a research funded by the Department of Safety and Health (Regional Government of the Junta de Andalusia). We analyze the concept of "prevention culture" in education. Therefore, the conclusions obtained in this paper, show the need to mainstream the concept of "safety", "health", etc. as fields of preventive action in the school context, key i ssues to consider in the teaching and learning process.